Randomized controlled trial of a pictorial aid intervention for medication adherence among HIV-positive patients with comorbid diabetes or hypertension. Issue 2 (1st February 2018) - Monroe, A. K.; Pena, J. S.; Moore, R. D.; Riekert, K. A.; Eakin, M. N.; Kripalani, S.; Chander, G.
ABSTRACT: As the HIV-infected population ages and the burden of chronic comorbidities increases, adherence to medications for HIV and diabetes and hypertension is crucial to improve outcomes. We pilot-tested a pictorial aid intervention to improve medication adherence for both HIV and common chronic conditions. Adult patients with HIV and diabetes (DM) and/or hypertension (HTN) attending a clinic for underserved patients and at risk for poor health outcomes were enrolled. Patients were randomized to receive either a pictorial aid intervention (a photographic representation of their medications, the indications, and the dosing schedule) or a standard clinic visit discharge medication list. Adherence to antiretroviral therapy (ART) for HIV and therapy for DM or HTN was compared. Predictors of ART adherence at baseline were determined using logistic regression. Medication adherence was assessed using medication possession ratio (MPR) for the 6-month interval before and after the intervention. Change in adherence by treatment group was compared by ANOVA. Among the 46 participants, there was a trend towards higher adherence to medications for HIV compared with medications for hypertension/diabetes (baseline median MPR for ART 0.92; baseline median MPR for the medication for the comorbid condition 0.79, p  = 0.07). The intervention was feasible to implement and satisfaction with the intervention was high. With a small sample size, the intervention did not demonstrate significant improvement in adherence to medications for HIV or comorbid conditions. Patients with HIV are often medically complex and may have multiple barriers to medication adherence. Medication adherence is a multifaceted process and adherence promotion interventions require an approach that targets patient-specific barriers.